A Primer on Juvenile Protective Legislation. (June 2014) - Abrams, Douglas E.
Abstract: The parens patriae doctrine is grounded in the proposition that children sometimes need the law's protection from their own improvidence or immaturity, and sometimes even from the conduct of their parents or other caretakers. Parens patriae underlies much state and federal regulation in such areas as abuse, neglect, foster care, adoption, medical decisionmaking, support, and delinquency. The doctrine also underlies the wide range of protective legislation that regulates children's conduct, the subject of this article.